Assessing the Effect of Work Ethic, Job Satisfaction, and Organizational Support on Employee Performance through Organizational Commitment at PT Menthobi Mitra Lestari Pangkalan Bun - Setyorini, Winarti; Hwihanus (International Journal of Science and Society, 2024)
In the era of globalization and digitalization, the world of work is experiencing significant changes that affect various aspects of the organization, including work ethic, job satisfaction, organizational support, organizational commitment, and employee performance. This study aims to analyze the effect of work ethic, job satisfaction, and organizational support on organizational commitment and employee performance, with organizational commitment as an intervening variable. Data were collected through a 5-point Likert questionnaire distributed to employees of PT Menthobi Mitra Lestari Pangkalan Bun and analyzed using SMARTPLS. The results showed that work ethic and organizational support have a positive and significant effect on organizational commitment, but job satisfaction has no significant effect. In addition, organizational commitment has no significant effect on employee performance. The study also found that organizational commitment does not moderate the effect of work ethic, job satisfaction, and organizational support on employee performance. However, work ethic has a positive and significant effect on employee performance, while job satisfaction and organizational support have no significant effect. These findings indicate that organizational support is an important factor in increasing organizational commitment, and work ethic directly affects employee performance. This research contributes to the human resource management literature by highlighting the importance of work ethic and organizational support in the context of employee performance.